CHEMICAL COMPOSITION OF ATMOSPHERES OF COOL GIANT STARS - Komarov, N. S. (Одеські астрономічні публікації, 2017)
Results of determination of abundances of chemical elements in the atmospheres of 57 giant stars of the oxygen sequence of the Galactic disk axe given. A brief survey of findings is presented making it possible to draw conclusion on evolution of abundances of chemical elements in the atmospheres of cool stars at the transition stages from the main sequence (MS) to that of the red giant (FRGB), from the upper boundary of a giant branch to the horizontal one, and eventually, at the stage of asymptotic giant branch (AGB). The rate of stellar evolution, efficiency of mixing depends on initial mass of the stars and primordial chemical composition of the progenitor matter.